Observations & Reflections on Texas Folklore - Abernethy, Francis Edward; Open Access Publishing in European Networks; Project Muse. (Texas A & M University Press [distributor], 2000)
Annotation Observations and Reflections, the title of the Texas Folklore Society's thirty-seventh numbered volume, is a collection of fourteen essays on Texas folklore and folk life. This volume gets its name from its lead article by Texas's leading folklorist, the late J. Frank Dobie.
Description based on print version record.
Keywords: Social Science -- Folklore & Mythology; Folklore -- United States; Electronic book; Electronic books